Shielding assessment in two computed tomography facilities in South-South Nigeria: How safe are the personnel and general public from ionizing radiation? - Omojola, Akintayo Daniel; Omojola, Funmilayo Ruth; Akpochafor, Michael Onoriode; Adeneye, Samuel Olaolu (The ASEAN Journal of Radiology, 2020)
Objective: The aims of this study were to estimate the instantaneous dose rate(IDR) and annual dose rate (ADR) to radiation staff and the general public withinthe controlled and supervised areas, respectively, to determine the shieldingdesign goals (P) of the 2 CT facilities and to determine the average annual dose(AD) to radiographer/operator in the control console during CT scans. Materials and Methods: The equipment used in this study consisted of twonewly installed General Electric (GE) Revolution ACTs CT machines. Technicalparameters used were a thoracic/dorsal spine scan, which was rarely done in both facilities. A calibrated Inspector USB (S.E. International, Inc.) survey meter was positioned < 50 cm from each barrier at various points to determine the average shielded air kerma Results: The average background radiation in the 2 facilities was 0.11 ?Sv/hr. The average ADR to the controlled and supervised areas in CT1 was 0.563±0.25 and 0.369±0.11 mSv/yr, respectively. Also, the average ADR to the controlled and supervised areas in CT2 were 0.410±0.28 and 0.354±0.04 mSv/yr, respectively. The average shielding design goal to the controlled and supervised areas for CT1 was 0.00898±0.0041 and 0.0059±0.0028 mSv/Week, respectively. Similarly, the average shielding design goal for the controlled and supervised areas for CT2 was 0.0066±0.0044 and 0.0057±0.0019 mSv/Week respectively. The estimated average AD to the operator in CT1 and CT2 was 2.5 and 1.3 ?Sv, respectively. Conclusion: The average ADR and shielding design goals in the controlled and supervised areas from both CTs were within acceptable limits for radiation staff and the public.